Molecular Detection and Phylogenetic Analysis of Endosymbiont Wolbachia pipientis (Rickettsiales: Anaplasmataceae) Isolated from Dirofilaria immitis in Northwest of Iran - Majid Khanmohammadi; Reza Falak; Ahmad Reza Meamar; Mehdi Arshadi; Lame Akhlaghi; Elham Razmjou (Tehran University of Medical Sciences, 2019)
Background: The purpose of this study was molecular detection and phylogenetic analysis of Wolbachia species of Dirofilaria immitis. Methods: Adult filarial nematodes were collected from the cardiovascular and pulmonary arterial systems of naturally infected dogs, which caught in different geographical areas of Meshkin Shahr in Ardabil Province, Iran, during 2017. Dirofilaria immitis genomic DNA were extracted.  Phylogenetic analysis for proofing of D. immitis was carried out using cytochrome oxidase I (COI) gene. Afterward, the purified DNA was used to determine the molecular pattern of the Wolbachia surface protein (WSP) gene sequence by PCR. Results: Phylogeny and homology studies showed high consistency of the COI gene with the previously-registered sequences for D. immitis. Comparison of DNA sequences revealed no nucleotide variation between them. PCR showed that all of the collected parasites were infected with W. pipientis. The sequence of the WSP gene in Wolbachia species from D. immitis was significantly different from other species of Dirofilaria as well as other filarial species. The maximum homology was observed with the Wolbachia isolated from D. immitis. The greatest distance between WSP nucleotides of Wolbachia species found between D. immitis and those isolated from Onchocerca lupi. Conclusion: PCR could be a simple but suitable method for detection of Wolbachia species. There is a pattern of host specificity between Wolbachia and Dirofilaria that can be related to ancestral evolutions. The results of this phylogenetic analysis and molecular characterization may help us for better identification of Wolbachia species and understanding of their coevolution.